Climate Signatures on Lake And Wetland Size Distributions in Arctic Deltas. Issue 20 (19th October 2021) - Vulis, Lawrence; Tejedor, Alejandro; Zaliapin, Ilya; Rowland, Joel C.; Foufoula‐Georgiou, Efi
Abstract: Understanding how thermokarst lakes on arctic river deltas will respond to rapid warming is critical for projecting how carbon storage and fluxes will change in those vulnerable environments. Yet, this understanding is currently limited partly due to the complexity of disentangling significant interannual variability from the longer‐term surface water signatures on the landscape, using the short summertime window of optical spaceborne observations. Here, we rigorously separate perennial lakes from ephemeral wetlands on 12 arctic deltas and report distinct size distributions and climate trends for the two waterbodies. Namely, we find a lognormal distribution for lakes and a power‐law distribution for wetlands, consistent with a simple proportionate growth model and inundated topography, respectively. Furthermore, while no trend with temperature is found for wetlands, a statistically significant decreasing trend of mean lake size with warmer temperatures is found, attributed to colder deltas having deeper and thicker permafrost preserving larger lakes. Plain Language Summary: Arctic river deltas are landscapes facing significant risk from climate change, in part due to their unique permafrost features. In particular, thermokarst lakes in ice‐rich permafrost are expected to both expand and drain under warming‐induced permafrost thaw, reconfiguring deltaic hydrology and impacting the arctic carbon cycle. A limitation in understanding how thermokarst lake cover might be changing is the significant interannual variability in water cover in flat regions such as deltas, which makes it difficult to distinguish between perennially inundated, thermally relevant waterbodies, and ephemerally inundated waterbodies. Here, we present a pan‐Arctic study of 12 arctic deltas wherein we classify observed waterbodies into perennial lakes and ephemeral wetlands capitalizing on the historical record of remote sensing data. We provide evidence that thermokarst lake sizes are universally lognormally distributed and that historical temperature trends are encoded in lake sizes, while wetland sizes are power law distributed and have no temperature trend. These findings pave the way for quantitative insight into lake cover changes on arctic deltas and associated carbon and hydrologic cycle impacts under future climate change. Key Points: Lake areas in arctic deltas exhibit a lognormal distribution associated with a simple mechanistic growth process Wetland areas exhibit a power law distribution consistent with inundated topography Colder arctic deltas have larger average lake sizes, likely due to thicker permafrost restricting sub‐lake hydrologic connectivity